Enabling knowledge societies in developing countries: the example of genomics. (10th February 2006) - Persad, Deepa L.; Quach, Uyen; Thorsteinsdottir, Halla; Salamanca-Buentello, Fabio; Singer, Peter; Daar, Abdallah
To address the health needs of developing countries, it is necessary to build and strengthen knowledge societies. By using genomics as an example, we aim to demonstrate that creating effective knowledge societies requires transformative steps and concrete mechanisms. We present four transformative steps towards the development of an expansive outlook regarding equity: developing a global state of mind; promoting long-term self-interests; facilitating public engagement and enhancing the production of Global Public Goods (GPGs) using the example of genomics knowledge. In support of these steps, we identify concrete mechanisms as an action plan using four pragmatic solutions: foresight exercises for identifying needs and prioritising technologies; strengthening capacity and improving access to knowledge in developing countries; defining intellectual property and regulatory concerns for these technologies; and establishing global governance and financial mechanisms.